From Wealth to Waste: The Environmental Toll of Gold Mining in Ghana - Musah, Baba Imoro (Universitas Ahmad Dahlan, 2025)
Background: The gold mining industry has been pivotal in driving Ghana's economic expansion and development. This sector has substantially influenced the national economy, generating significant revenue and employment opportunities. Furthermore, the financial resources accrued have enabled investments in critical domains, fostering national progress. This review provides a nuanced examination of the socioeconomic implications of gold mining in Ghana, offering insights to inform policymaking and promote sustainable practices. Method: Extensive literature reviews were conducted across a wide range of leading academic databases, including ScienceDirect, PubMed, Google Scholar, JSTOR, Web of Science, EMBASE, and Scopus, to thoroughly investigate the relevant research on this topic. Results: The gold mining industry generates substantial revenue and employment, yet the perceived benefits inadequate compared to its economic output. The sector has failed to consistently improve local livelihoods, with communities reporting a lack of corresponding enhancements in their standard of living. Significant concerns persist regarding environmental degradation, displacement of residents, and inequitable profit distribution. This analysis underscores the urgent need for stronger enforcement of environmental regulations and greater accountability and equity within the sector. Furthermore, there is a stark disconnect between the wealth generated by gold mining and the adverse effects on mining communities, which face grave health and socio-economic challenges due to environmental degradation. Conclusion: This review emphasizes the pressing necessity for implementing sustainable gold mining practices in Ghana to mitigate environmental degradation. Fostering effective collaboration among all stakeholders is pivotal to achieving sustainable mining operations and the equitable distribution of mineral wealth.